Clomipramine for Compulsive Tics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Reduction of adventitious movements and compulsions during clomipramine treatment (25 mg - 200 mg daily at bedtime) in five prepubertal, autistic, retarded boys is reported from the Division of Child and Adolescent Psychiatry, Bellevue Hospital and New York University Medical Center, New York.